Analisis Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan dan Kebijakan Dividen Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Moderasi - Rani Miranda Sagita; Iwan Kusuma Negara; Iwan Kusmayadi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
This study aims to analyze the effect of Profitability, Liquidity, Company Size and Dividend Policy on Firm Value with Capital Structure as a moderating variable in property and real estate sector companies listed on the IDX for the 2017-2021 period. The type of research used is associative research with a quantitative approach. The population in this study are all property and real estate sector companies listed on the Indonesia Stock Exchange totaling 83 companies. Sampling in this study using the method purposive sampling with certain criteria, namely as many as 8 companies. The analytical tools used are descriptive statistical tests, classic assumption tests, hypothesis testing and Moderated Regression Analysis (MRA). The results of this study indicate that Profitability (ROA) and Dividend Policy (DPR) have a not significant positive effect on Firm Value (PBV), Liquidity (CR) have an insignificant negative effect on Firm Value and Firm Size (SIZE) have a significant negative effect on firm value. Capital Structure (DER) is not able to moderate the effect of Profitability, Liquidity and Firm Size on Firm Value. However, it is able to moderate the effect of dividend policy on firm value